Pengaruh Burnout, Stres Kerja Dan Beban Kerja Terhadap Kinerja Perawat Pada RS Tk III Reksodiwiryo Padang - Apria Darma; Lasti Yossi Hastini (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to determine the effect of burnout, work stress and workload on nurse performance at RS TK III Reksodiwiryo Padang. The population in this study were all nurses at Dr. Reksodiwiryo Padang Hospital totaling 201 people. The sample in this study was 127 people. This study is a quantitative study. The instrument used in this study was a questionnaire. The results of the study using multiple linear regression analysis showed that simultaneously there was a negative and significant effect on the burnout and workload variables on nurse performance and the work stress variable had a significant effect on nurse performance